2019
DOI: 10.3390/cancers11040520
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Inconsistencies in Using Lysophosphatidic Acid as a Biomarker for Ovarian Cancer

Abstract: Increased detection of plasma lysophosphatidic acid (LPA) has been proposed as a potential diagnostic biomarker in ovarian cancer, but inconsistency exists in these reports. It has been shown that LPA can undergo an artificial increase during sample processing and analysis, which has not been accounted for in ovarian cancer research. The aim of this study is to provide a potential explanation about how the artificial increase in LPA may have interfered with previous LPA analysis in ovarian cancer research. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Several studies have found a relationship between plasma LPA levels and ovarian carcinoma; for example, a meta-analysis, comparing LPA levels in the serum of 980 ovarian cancer patients, 872 benign controls and 668 healthy controls, showed higher LPA plasma levels in the cancer group with respect to the benign and healthy control samples [146], thus suggesting that the raised detection of plasma LPA might be a potential diagnostic biomarker. Nonetheless, this finding is not supported by a recent lipidomic study that did not find any change in the content of this lipid in serum of ovarian cancer patients [147]. Discrepancies in the results can be explained taking into the account that, due to its susceptibility to sample processing procedure (e.g., plasma storage time at room temperature and anticoagulant used for blood drawing), LPA can artificially increase.…”
Section: Platelet-derived Bioactive Compoundsmentioning
confidence: 64%
“…Several studies have found a relationship between plasma LPA levels and ovarian carcinoma; for example, a meta-analysis, comparing LPA levels in the serum of 980 ovarian cancer patients, 872 benign controls and 668 healthy controls, showed higher LPA plasma levels in the cancer group with respect to the benign and healthy control samples [146], thus suggesting that the raised detection of plasma LPA might be a potential diagnostic biomarker. Nonetheless, this finding is not supported by a recent lipidomic study that did not find any change in the content of this lipid in serum of ovarian cancer patients [147]. Discrepancies in the results can be explained taking into the account that, due to its susceptibility to sample processing procedure (e.g., plasma storage time at room temperature and anticoagulant used for blood drawing), LPA can artificially increase.…”
Section: Platelet-derived Bioactive Compoundsmentioning
confidence: 64%
“…We have also found less abundant phospholipids such as phosphatidylglycerol (PG) and phosphatidylserine (PS), but did not include them in this study due to their insufficient peak intensities, which may be inconsistently detected when interfered by more abundant ions. We also detected LPA and LPI, which we found to be unstable, resulting in exclusion from our study [13].…”
Section: Lc-ms Analysis Of Lysophospholipidsmentioning
confidence: 87%
“…While studies using global lipidomics approaches have reported different plasma phospholipids profiles in ovarian cancer patients, these findings were limited by unsatisfactory sensitivity and/or an absence of benign tumor [9][10][11][12]. Furthermore, the sole use of lysophosphatidic acid (LPA), the most intensively studied phospholipid, also has significant limitations due to the artificial increase during sample processing, storage, and analysis [13].…”
Section: Introductionmentioning
confidence: 99%
“…There have been some contradictory reports, however, as Baker and colleagues reported that there were no significant differences in the concentrations of either individual LPA values or total LPA in the plasma of ovarian cancer patients compared to normal controls (Baker et al, 2002) and, recently, it was reported that LPA levels were lower in the plasma of ovarian cancer patients (Yagi et al, 2019). These discrepancies have been suggested to be due to the fact that LPA levels in plasma can be artificially increased during sample handling and processing (Yagi et al, 2019). Our data would indicate that total plasma LPA levels per se are not biomarkers for HNSCC.…”
Section: Discussionmentioning
confidence: 99%